2019
DOI: 10.1111/1462-2920.14738
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of Trebouxiophyceae diversity explored by high‐throughput sequencing and phylogenetic approaches

Abstract: Summary Trebouxiophyceae are a ubiquitous class of Chlorophyta encountered in aquatic and terrestrial environments. Most taxa are photosynthetic, and many acts as photobionts in symbiotic relationships, while others are free‐living. Trebouxiophyceae have also been widely investigated for their use for biotechnological applications. In this work, we aimed at obtaining a comprehensive image of their diversity by compiling the information of 435 freshwater, soil and marine environmental DNA samples surveyed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…However, they were probably often overlooked in monitoring programs of investigation for water quality because of its cell size (<3 μm). In contrast, Metz et al ( 2019 ) mostly found C. limnetica in freshwater and soil samples collected around the world. Both other species were not reported in that study, which could be the result of the intron distribution described above.…”
Section: Discussionmentioning
confidence: 94%
“…However, they were probably often overlooked in monitoring programs of investigation for water quality because of its cell size (<3 μm). In contrast, Metz et al ( 2019 ) mostly found C. limnetica in freshwater and soil samples collected around the world. Both other species were not reported in that study, which could be the result of the intron distribution described above.…”
Section: Discussionmentioning
confidence: 94%
“…Coccomyxa Schmidle -This trebouxiophycean algal genus is notable for the diversity of habitats and ecological circumstances in which its species are known to occur. Environmental surveys have found Coccomyxa sequences to be among the most widely distributed OTUs, and notably well represented in cold highlatitude climates (Metz et al 2019). It is commonly reported freeliving on terrestrial substrata and in aquatic environments, including those highly polluted with heavy metals and radioactive materials (see Gustavs et al 2017).…”
Section: Cyanobacteriamentioning
confidence: 99%
“…In the last years, several new lineages of trebouxiophycean algae have been discovered including the description of new genera, suggesting that the diversity of this group is still underexplored (Neustupa et al 2013;Song et al 2015;Vančurová et al 2015;Ulrich and Röske 2018;Darienko and Pröschold 2019). This goes along with a recent metagenomic study showing that the most diverse trebouxiophycean communities are found in freshwater and soil environments (Metz et al 2019). Like in the present study, integrative taxonomic approaches combining morphological and molecular traits will improve the knowledge about biodiversity in the diverse class of Trebouxiophyceae (e.g., Muggia et al 2018).…”
Section: Discussionmentioning
confidence: 91%